Two new species of Astyanax (Characiformes: Characidae) from upper rio Paraguaçu and rio Itapicuru basins, Chapada Diamantina, Bahia, Brazil - Zanata, Angela M.; Camelier, Priscila (Zootaxa, 2008)
Two new characid species, Astyanax epiagos, from the upper rio Jacuípe, rio Paraguaçu basin, and A. jacobinae, from the upper rio Itapicuru-mirim, rio Itapicuru basin, Chapada Diamantina, Bahia, Brazil, are described. Astyanax epiagos is distinguished from the majority of its congeners and from all Astyanax known to occur in northeastern Brazilian drainages by the reduced number of branched anal-fin rays (usually 14-16), along with a series of other distinctive characters (e.g., vertically elongated humeral blotch, conspicuous dark blotch over caudal peduncle, absence of conspicuous midlateral dark stripe, body highest around vertical through midlength of pectoral-fin, absence of scales over anal-fin base, presence of broad naked space between infraorbitals and preopercle). Astyanax jacobinae differs from its congeners by a combination of morphometric, meristic, and pigmentary characters (e.g., large eye diameter, three maxillary teeth, presence of a vertically elongated humeral blotch, absence of a conspicuous dark midlateral stripe or conspicuous spot over caudal peduncle, absence of broad naked space between infraorbitals and preopercle).